Modigiz Application as an Educational Media for Overweight Teenagers - Retno Wahyu Ningsih; Joyeti Darni; Ramadan Wibi Surya Aji (Jurnal Gizi Prima (Prime Nutrition Journal), 2023)
Background: Android mobile applications about nutrition and health are starting to be developed, but only a few develop mobile applications with a discussion of overweight adolescents. Android media with exciting features can be an alternative to increase adolescents' awareness of the problem of obesity.Research Methods: Development of an Android mobile application named "Modigiz," which stands for mobile obesity diet nutrition. The application is developed using the agile software development method and uses its development technology, namely Android Studio, Android SDK, Kotlin, Android Jetpack Library, Github, Figma, and Canva.Research Result: The Modigiz application implements the principle of quick feedback for application users. Users can find nutritional status information about each feature display, and there is feedback for consultations between users and the team via WhatsApp no.Conclusion: The Modigiz application was developed for overweight adolescents to monitor their nutritional status and manage their diet independently. In addition, this application also provides nutrition and health information for users, so it is hoped that it can encourage healthy behavior habits and implement balanced nutrition.